THE FIRST YEARS OF TEACHING AND THE DIFFICULTIES OF BEGINNING TEACHERS WHO TEACH MATHEMATICS INSIDE MATO GROSSO SOUTH STATE - Ciriaco, Klinger Teodoro [UNESP]; Miotto Morelatti, Maria Raquel [UNESP]; Ponte, Joao Pedro da (Univ Federal Mato Grosso Sul, 2019)
The general objective of this article is to present data from a doctoral research, fruit of the first author's thesis, linked to the Graduate Program in Education of FCT / UNESP, Presidente Prudente-SP. To this end, it is intended to bring up narratives of five beginning teachers about their difficulties facing the process of insertion in the teaching career. Four are graduates in Pedagogy and one in Mathematics. This is a qualitative research, in the modality of strategic action research, in which the problematization of the experiences of the first years in the profession are motto for raising indicators to overcome difficulties faced based on the possibility of constituting a working group with collaborative characteristics. The results showed indications of the potential of the possibility of sharing experience between pedagogues and mathematics teachers.
Keywords: Teacher Training; Beginning of Teaching; Mathematics teaching; Pedagogical / conceptual difficulties; Collaboration